Impaired cocaine‐induced behavioral plasticity in the male offspring of cocaine‐experienced sires. (6th January 2019) - Wimmer, Mathieu E.; Vassoler, Fair M.; White, Samantha L.; Schmidt, Heath D.; Sidoli, Simone; Han, Yumiao; Garcia, Benjamin A.; Pierce, R. Christopher
Abstract: Our previous work indicated that male, but not female, offspring of cocaine‐experienced sires display blunted cocaine self‐administration. We extended this line of investigation to examine behavioral sensitization, a commonly used model of cocaine‐induced behavioral and neuronal plasticity. Results indicated that male, but not female, offspring of cocaine‐taking sires showed deficits in the ability of repeated systemic cocaine injections to induce augmented locomotor activity. The reduced cocaine sensitization phenotype in male progeny was associated with changes in histone post‐translational modifications, epigenetic processes that regulate gene expression by controlling the accessibility of genes to transcriptional machinery, in the nucleus accumbens of first‐generation male progeny. Thus, five histone post‐translational modifications were significantly altered in the male progeny of cocaine‐exposed sires. In contrast, self‐administration of nicotine was unaltered in male and female offspring suggesting that the intergenerational effects of paternal cocaine taking may be drug‐specific. Interestingly, the reduced sensitivity to cocaine previously observed in the male offspring of cocaine‐taking sires dissipated in the grand‐offspring. Both male and female grand‐progeny of cocaine‐exposed sires showed unaltered cocaine‐induced behavioral sensitization and cocaine self‐administration. Taken together, these findings indicate that paternal cocaine taking produces changes in multiple cocaine addiction‐related behaviors in male progeny, which do not persist beyond the first generation of offspring. Moreover, the altered sensitivity to cocaine in first‐generation male progeny of cocaine‐sired male offspring was associated with epigenetic modifications in the nucleus accumbens, a nucleus that plays a critical role in cocaine‐associated behavioral plasticity. Abstract : Male first‐generation progeny of sires that chronically self‐administered cocaine show lower cocaine sensitivity and changes in histone post‐translational modifications in the nucleus accumbens. In contrast, second‐generation offspring of cocaine‐taking sires show unaltered cocaine self‐administration and cocaine behavioral sensitization. These data indicate that paternal cocaine exposure confers altered cocaine sensitivity in male offspring but not in subsequent generations.